PENGEMBANGAN E-MODUL METODE TOTAL PHYSICAL RESPONSE DALAM MENGENALKAN KOSAKATA PADA ANAK USIA 4-5 TAHUN DI TK NUSA INDAH, DESA TOTO UTARA, KEC. TILONGKABILA, GORONTALO - Suryani, Ni Putu Lilis; Utoyo, Setiyo; Jamin, Nunung Suryana; Juniarti, Yenti (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2024)
This research was carried out with the aim of being a learning solution by developingan E-Module Total Physical Response (TPR) method in introducing vocabularyto children aged 4-5 years (development research in group A, Nusa Indah Kindergarten,North Toto Village, Tilongkabila District, Kab. Bone Bolango, Gorontalo).The method used in this study is a research and development method with the Hannafinand Peck model. In collecting data using observation, interviews, documentationand questionnaires in the form of questionnaires. The results of the expert validationtest showed that 83%, with the E-Modul product category, was very suitablefor use in learning. In the small group trial by the teacher, it got a percentage scoreof 89%, with the E-Modul product category being very well used in the learningprocess. The small group trial on children got a score of 3, with the E-Modul productcategory being good for use in the learning process. As for the field trial, the teachergot a percentage score of 90%, with the E-Modul product category being very wellused in learning. And field trials on children got a score of 3, with the E-Modulproduct category being good for use in learning. Based on the trial data, the developmentof the E-Modul Total Physical Response learning method provides benefitsto children by developing the six aspects of child development.